1981
DOI: 10.1128/jvi.38.3.805-814.1981
|View full text |Cite
|
Sign up to set email alerts
|

Polyoma virus minichromosomes: a soluble in vitro replication system

Abstract: Polyoma virus minichromosomes were isolated from infected 3T6 cells by hypotonic extraction of isolated nuclei. The kinetics of in vitro DNA synthesis in the nuclear extract was similar to that observed with intact nuclei. The majority of the products of in vitro DNA synthesis sedimented with replicative intermediate (RI) minichromosomes and migrated as two bands (RI-a and RI-b) on 1.4% agarose gels. The kinetics of deoxynucleotide monophosphate incorporation into these species was consistent with the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The first possibility cannot be ruled out because about 10% of the products are probably this system to initiate replication on an exoge-derived from the repair-type reaction as evinous template is in contrast to all previously denced by the density transfer experiment. reported subcellular DNA replication systems of However, all of the form III DNA, which was SV40, which in vitro could only elongate the about 36% of the total product in the alkaline strands initiated in vivo (5,6,12,34).…”
Section: Discussionmentioning
confidence: 99%
“…The first possibility cannot be ruled out because about 10% of the products are probably this system to initiate replication on an exoge-derived from the repair-type reaction as evinous template is in contrast to all previously denced by the density transfer experiment. reported subcellular DNA replication systems of However, all of the form III DNA, which was SV40, which in vitro could only elongate the about 36% of the total product in the alkaline strands initiated in vivo (5,6,12,34).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we classify the DNA structures and quantitate RI DNA molecules found in fractions of the polyoma minichromosome gradients of Gourlie et al (14). To determine the absolute concentrations of replicating and nonreplicating polyoma DNA molecules, we used the technique of quantitative electron microscopy (3,5,19,21).…”
mentioning
confidence: 99%
“…1). The thymidine incorporation data coupled with data from earlier electron microscopic studies of similar gradients (11,19) indicated that fractions 5 to 10 represented the replicative intermediate (RI) region of the gradient, whereas mature minichromosomes sedimented in fractions 10 to 15. Fractions were subsequently assayed for poly(ADP-rib) polymerase activity by using endogenous acceptors.…”
Section: Resultsmentioning
confidence: 75%